Hiperreality Political Communication, Pop Culture and First Time Voters: Content Analysis Tiktok @erick.thohir - Asri, Rahman (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The purpose of this study is to describe a strategy of pop culture that is used to shape the self-image of a political actor who is depicted through electronic media, especially the use of social media TikTok which is part of a political communication channel. The author wants to examine the hyperreality of political communication constructed by the official TikTok account @erickthohir as a presidential-vice presidential candidate in the upcoming 2024 General Election. Using a constructivist paradigm with content analysis methods and a qualitative approach, this study relates to Jean Baudrillard's (1994) thinking about the hyperreality of post content by Erick Thohir's campaign team with is themes or topics that are currently viral, trending topics on social media, expressions, choreography/dance by involving public figures, influencers, celebgrams, Youtubers, with direct, informal, and popular gimmick delivery to strengthen personal branding especially for beginner voters who are potential targets in the upcoming 2024 results of this study indicate that the campaign team for the presidential and vice-presidential candidates optimally by using popular culture idioms and gimmicks and forming (hyperreality) in the image of a figure that is presented as if in the 'real' world depicted in post content count. Official TikTok @erick.thohir. The research shows that studies related to self-im personal branding and other media effects in political communication continue to be used by optimizing the use of social media as an alternative medium for campaigning.